ANALISIS PENGARUH NILAI TUKAR RUPIAH PER DOLLAR AS, TINGKAT SUKU BUNGA SBI, DAN INFLASI INDEKS HARGA KONSUMEN (IHK) TERHADAP IHSG DI BEI PERIODE 2003 – 2008 - Kurnia, Fransisca; Santioso, Linda (Jurnal Ekonomi, 2010)
Financial statement is an important thing for a company. The financial statement of the company can indicate the company's condition and the investors always wait it for setting their investments. The purpose of this survey is to observe whether Rupiah exchange rate per US Dollars, Interest rate of SBI and Inflation of Consumer Price Index (CPI) have influence Composite Stock Price Index at Jakarta Stock Exchange either through partial and also simultan. The result shows that variable of Interest rate of SBI and Inflation of Consumer Price Index (CPI) significantly influence on the Composite Stock Price Index. If it is analyzed simultaneously, three variables have significant influences on the Composite Stock Price Index.